Do you get the message? Defining the interpreter’s role in medical interpreting in Belgium - Cox, Antoon (MonTi Monografías de Traducción e Interpretación, 2016)
This paper aims to investigate the field-level realities of the codes of conduct adhered to by different agencies in Belgium for community interpreters, and the degree of interpreter discretion in the application of these codes. We focus on the specific setting of the health care sector in Brussels, where community interpreters and intercultural mediators sent out by different agencies often operate in the same hospitals. Drawing on data obtained through participant observation, interviews with key actors in the field and desk research, we analyze how the codes of conduct applied by different agencies affect multilingual and intercultural communication in a hospital context, in particular at those levels of the communication process where misunderstandings occur most often.